Making History: the Australian history curriculum and national identity. (2nd July 2021) - Fozdar, Farida; Martin, Catherine Ann
Abstract : History is a key site for the negotiation of national identity, with the ability to define the past shaping the national narrative on who "we" were, who "we" are, and, crucially, who "we" should be. As such, the teaching of history is a site of intense political debate. This paper examines the history module of the Australian Curriculum to understand the extent to which the history curriculum moves beyond Eurocentric, colonial imaginings of Australia's history towards a more inclusive, multi‐cultural, globally‐oriented, cosmopolitan vision of society. Both the curriculum and teaching resources were examined to ascertain the identities and orientations these materials could provide. The research finds that — despite improvements in presenting a diversity of representations, in particular a positive focus on the rights and contributions of Indigenous peoples in Australia and some orientation to diverse migrant histories, the environment, and Asia — the main thrust of the curriculum is a focus on the nation‐state at the expense of global engagement. The funnel structure which deals with broader world history in earlier years, relegates the rest of the world to a temporal and spatial distance, leaving a somewhat myopic narrative that perpetuates traditional, Anglo‐centric narratives, maintaining the perspectives of "Others" as peripheral.